Desain Sistem, Job Order Costing - Muhammad Idris DM (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2019)
Management accounting is a financial information processing system that is used to produce financial information for the interests of the organization's internal users. As one type of information, management accounting is a type of quantitative information that uses money as a unit of measurement, which is used to assist management in implementing company management. Management accounting is financial information which is the output produced by the type of management accounting, which is used primarily by internal users of the organization. Process costing systems are used in companies that produce one type of product in large quantities in the long run. The basic principle of the costing process is accumulating costs from certain operations or departments during a full period (monthly, quarterly, and yearly) and then dividing by the number of units produced during that period. The Job Order Costing system is also widely used in service companies. Like hospitals, legal consultant offices, cinema studios, accountant offices, ad agencies, repair shops use a system of collecting fees with job order costs for accounting and billing purposes. The problem of recording and charging costs will be more complex when the company sells various kinds of products and services.